Gravimetric and volumetric determination of the purity of electrolytically refined silver and the produced silver nitrate - Ačanski Marijana M.; Savatović Slađana M.; Radić Mira D. (Hemijska Industrija, 2007)
Silver is, along with gold and the platinum-group metals, one of the so called precious metals. Because of its comparative scarcity, brilliant white color, malleability and resistance to atmospheric oxidation, silver has been used in the manufacture of coins and jewelry for a long time. Silver has the highest known electrical and thermal conductivity of all metals and is used in fabricating printed electrical circuits, and also as a coating for electronic conductors. It is also alloyed with other elements such as nickel or palladium for use in electrical contacts. The most useful silver salt is silver nitrate, a caustic chemical reagent, significant as an antiseptic and as a reagent in analytical chemistry. Pure silver nitrate is an intermediate in the industrial preparation of other silver salts, including the colloidal silver compounds used in medicine and the silver halides incorporated into photographic emulsions. Silver halides become increasingly insoluble in the series: AgCl, AgBr, AgI. All silver salts are sensitive to light and are used in photographic coatings on film and paper. The ZORKA-PHARMA company (Sabac, Serbia) specializes in the production of pharmaceutical remedies and lab chemicals. One of its products is chemical silver nitrate (argentum-nitricum) (l). Silver nitrate is generally produced by dissolving pure electrolytically refined silver in hot 48% nitric acid. Since the purity of silver nitrate, produced in 2002, was not in compliance with the p.a. level of purity, there was doubt that the electrolytically refined silver was pure. The aim of this research was the gravimetric and volumetric determination of the purity of electrolytically refined silver and silver nitrate, produced industrially and in a laboratory. The purity determination was carried out gravimetrically, by the sedimentation of silver(I) ions in the form of insoluble silver salts: AgCl, AgBr and Agi, and volumetrically, according to Mohr and Volhardt. The purity of electrolytically refined silver obtained volumetrically, according to Volhard, was 99.49%. The results suggest that the purity of electrolytically refined silver was higher than 99%. After all of these determinations, the purity of electrolytically refined silver was examined by atomic absorption spectrometry and the results confirmed that the purity of electrolytically refined silver was 99.99%. Electrolytically refined silver contained other metals: Mn, Cu, Fe, Zn, Pb, Cd, and the contents of these metals were: 1.15 ppm; 0.75 ppm; 0.65 ppm; 1.82 ppm; < 0.07 ppm and < 0.01 ppm, respectively.